The Structural Design, Kinematics, and Workspace Analysis of a Novel Rod–Cable Hybrid Cable-Driven Parallel Robot - Jinrun Li; Yangmin Li (Biomimetics)
This study presents a novel rod–cable hybrid planar cable-driven parallel robot inspired by the biological synergy of bones and muscles. The design integrates rigid rods and flexible cables to enhance structural stability and precision in motion control. The rods emulate bones, providing foundational support, while the cables mimic muscles, driving motion through coordinated tension. This design enables planar motions with three degrees of freedom, and a structural configuration that mitigates sagging and vibration for improved stability and accuracy by introducing rigid structure. The study develops detailed kinematic models, including Jacobian analysis for motion control, and evaluates the workspace using geometric and Monte Carlo methods.